RANCANG BANGUN ALAT PENGHITUNG BARANG OTOMATIS BERBASIS IOT UNTUK MONITORING PROSES PRODUKSI DI PABRIK - Dimas Dwi Saputra; Mohammad Ridwan; Sukrim (Universitas Islam Syekh Yusuf Tangerang, 2026)
This study aims to design and implement an automatic item counting system based on the Internet of Things (IoT) to improve production efficiency in contract-based manufacturing. The system is developed using a NodeMCU ESP32 microcontroller integrated with infrared and ultrasonic sensors to automatically detect item presence. The counting results are displayed through an I2C LCD and transmitted to a server for real-time monitoring via a web dashboard. Unlike previous studies that relied solely on single sensors without IoT integration, this system incorporates Fuzzy logic to improve detection accuracy at sensor threshold conditions while supporting remote monitoring. Testing was conducted using the Black Box Testing method to ensure all features function as intended. The results show that the system achieves an accuracy of 98.5%, with an average sensor response time of 1.2 seconds and a 100% success rate in data transmission to the web dashboard. Therefore, the proposed system demonstrates advantages over prior methods in terms of speed, accuracy, and ease of production monitoring